FOUNDATION RECOMMENDATIONS TO PROVIDE BEARING CAPACITY FOR ADDITIONAL FLOORS IN THE EAST JAKARTA PPKPPL BUILDING - Hutagaol, Kerlima; Dasuha, Ancient Betman; Gunawan, Hendra Ali; Muriya, Muriya (Universitas Dharmawangsa Medan, 2026)
This study aims to provide recommendations regarding foundations capable of supporting additional floors in the PPKPPL building in East Jakarta. The focus of this study is to assess the feasibility of the existing structure, especially the foundation elements, in line with the planned floor addition. A survey was conducted through visual and technical observations to determine the current condition of the structural elements. Data obtained from the survey were then analyzed using structural calculation methods to determine the foundation's capacity to accommodate gravity and earthquake loads in accordance with applicable standards. The analysis results indicate that the existing foundation's bearing capacity is insufficient to support the planned loads after the floor addition. If there is a mismatch between the foundation capacity and the new loads, recommendations for foundation repair or reinforcement will be provided so that the building can meet safety and comfort standards. It is hoped that this study can provide a basis for making technical decisions regarding additional floors and appropriate foundation reinforcement.